Analysis of Physical Enviromental Factors on the Risk of Stunting in Pregnant Women in the Working Area of the Curugbitung Health Center, Lebak Regency, Banten - Siauta, Jenny; Rukmaini; Yenny Aulya; Nazmi Hasanah (International Journal of Midwifery and Health Sciences, 2023)
Background: Stunting according to the WHO (World Health Organization) in 2019 that the region in sothest Asia is still considered the highest with the incidence of stunting (31.9%), Indonesia is included in the sixth country. Risk factors for stunting that begin at conception, namely from maternal factors. Lack of health and nutrition knowledge from the start of pregnancy to childbirth can result in stunting in children, during pregnancy ANC, PNC, EXCLUSIVE BREASTFEEDING, and MPASI. Objective: this study aims to determine the relationship between drinking water sources, latrine ownership, waste management, hygiene and exposure to pollutants with the risk of stunting in pregnant women in the working area of the Curugbitung Health Center, Lebak Regency, Banten. Methodology: Cross Seectional method research. The study sample amounted to 107 pregnant women. Purposive sampling technique. The research instrument using the questionnaire consisted of clean water use, latrine ownership, hygiene behavior, waste management and exposure to pollutants.this questionnaire has been tested for validity and reliability with a Cronbach's alpha coefficient value of 0.836. Research Results: there was a significant relationship between household water use (p = 0.000), latrine ownership (p = 0.30), waste management (p = 0.000), hygiene behavior (p = 0.001) and exposure to pollutants (p = 0.003) with stunting risk. Conclusions and suggestions: physical environment analysis factors have a significant relationship with the risk of stunting in pregnant women, so it is expected to increase the role of health workers to educate the public regarding the risk of stunting. Keywords: Physical Environment, Risk of Stunting